Fertility Trends, Patterns and Diffentials in Nepal - Thapa, Keshav (Patan Pragya, 2019)
Fertility is to give babies during the reproducing age (15-49 years) of women. It is directly related to women’s menstrual cycle beings. The main objective of this article to analyze the fertility trends, patterns and differential by different dimension. The required information are obtained from different secondary sources and analyzed and described meaningfully. The fertility level is gradually decreasing and it might be have by improvement of the socio-economic situation, health service facilities, enhance the education level of women and policy program of government are successfully implemented. Fertility is differential by residential area, ecological zone, education, caste/ethnic groups, religion etc.